Discourse of inculturation and decolonization of Christianity in KwaZulu Natal South Africa : a pentecostal missiological perspective - Mpofu, Buhle (University of Pretoria, 2025)
Dissertation (MTh (Mission Studies))--University of Pretoria, 2025.